Comparative proteomic analysis of drought tolerance in the two contrasting Tibetan wild genotypes and cultivated genotype - Wang, Nanbo (BMC Genomics, 2015)
BACKGROUND: Drought is one of major abiotic stresses constraining crop productivity worldwide. To adapt to drought stress, plants have evolved sophisticated defence mechanisms. Wild barley germplasm is a treasure trove of useful genes and offers rich sources of genetic variation for crop improvement. In this study, a proteome analysis was performed to identify the genetic resources and to understand the mechanisms of drought tolerance in plants that could result in high levels of tolerance to drought stress. RESULTS: A greenhouse pot experiment was performed to compare proteomic characteristics of two contrasting Tibetan wild barley genotypes (drought-tolerant XZ5 and drought-sensitive XZ54) and cv. ZAU3, in response to drought stress at soil moisture content 10 % (SMC10) and 4 % (SMC4) and subsequently 2 days (R1) and 5 days (R2) of recovery. More than 1700 protein spots were identified that are involved in each gel, wherein 132, 92, 86, 242 spots in XZ5 and 261, 137, 156, 187 in XZ54 from SMC10, SMC4, R1 and R2 samples were differentially expressed by drought over the control, respectively. Thirty-eight drought-tolerance-associated proteins were identified using mass spectrometry and data bank analysis. These proteins were categorized mainly into photosynthesis, stress response, metabolic process, energy and amino-acid biosynthesis. Among them, 6 protein spots were exclusively expressed or up-regulated under drought stress in XZ5 but not in XZ54, including melanoma-associated antigen p97, type I chlorophyll a/b-binding protein b, glutathione S-transferase 1, ribulosebisphosphate carboxylase large chain. Moreover, type I chlorophyll a/b-binding protein b was specifically expressed in XZ5 (Spots A4, B1 and C3) but not in both of XZ54 and ZAU3. These proteins may play crucial roles in drought-tolerance in XZ5. Coding Sequences (CDS) of rbcL and Trx-M genes from XZ5, XZ54 and ZAU3 were cloned and sequenced. CDS length of rbcL and Trx-M was 1401 bp (the partial-length CDS region) and 528 bp (full-length CDS region), respectively, encoding 467 and 176 amino acids. Comparison of gene sequences among XZ5, XZ54 and ZAU3 revealed 5 and 2 SNPs for rbcL and Trx-M, respectively, with two 2 SNPs of missense mutation in the both genes. CONCLUSIONS: Our findings highlight the significance of specific-proteins associated with drought tolerance, and verified the potential value of Tibetan wild barley in improving drought tolerance of barley as well as other cereal crops. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1657-3) contains supplementary material, which is available to authorized users.